Proof of Concept of a Breakwater-Integrated Hybrid Wave Energy Converter Using a Composite Modelling Approach - Theofano I. Koutrouveli (2021)
Despite the efforts of developers, investors and scientific community, the successful development of a competitive wave energy industry is proving elusive. One of the most important barriers against wave energy conversion is the efficiency of the devices compared with all the associated costs over the lifetime of an electricity generating plant, which translates into a very high Levelised Cost of Energy (LCoE) compared to that of other renewable energy technologies such as wind or solar photovoltaic. Furthermore, the industrial roll-out of Wave Energy Converter (WEC) devices is severely hampered by problems related to their reliability and operability, particularly in open waters and during harsh environmental sea conditions. WEC technologies in multi-purpose breakwaters-i.e., a structure that retains its primary function of providing sheltered conditions for port operations to develop and includes electricity production as an added co-benefit-appears to be a promising approach to improve cost-effectiveness in terms of energy production. This paper presents the proof of concept study of a novel hybrid-WEC (HWEC) that uses two well understood power generating technologies, air and water turbines, integrated in breakwaters, by means of a composite modelling approach. Preliminary results indicate: firstly, hybridisation is an adequate approach to harness the available energy most efficiently over a wide range of metocean conditions; secondly, the hydraulic performance of the breakwater improves; finally, no evident negative impacts in the overall structural stability specific to the integration were observed.